Estudo dos efeitos do biodiesel e suas misturas com óleo diesel em materiais metálicos - Kugelmeier, Cristie Luis (Universidade Federal de São Carlos, 2017)
The use of biodiesel in vehicles can significantly reduce dependence on fossil fuels and help to reduce environmental pollution. However, there are concerns about the compatibility of automotive materials in contact with biodiesel. Alloys of ferrous and non-ferrous metals that come in contact with the fuel may exhibit corrosive behavior because biodiesel, which has different chemical characteristics compared to diesel, may interact with materials in a different way. The objective of the study was to compare the corrosion behavior of SAE 8620 carbon steel; 13 Cr supermartensitic stainless steel; AA6061-T4 aluminum alloy with and without Equal-Channel Angular Pressing; copper and lead in three diesel/biodiesel binary blends (B7, B15 and B30). Mass loss tests were performed by total immersion, crevice corrosion, partial immersion and in contact with the vapor phase of each binary blends for 2160 h at 50 °C. The materials were evaluated through structural characterization, optical microscopy (OM), scanning electron microscopy (SEM) and X-ray dispersive energy (EDX), determination of metallic elements in the blends and corrosivity of the copper. The physicochemical characteristics of the mixtures were determined by oxidative stability analyzes at 110 °C, specific mass at 20 °C, kinematic viscosity at 40 °C, hydrogen and carbon nuclear magnetic resonance (1H and 13C) and ASTM color analysis. The results showed that copper and lead are materials not recommended for use in contact with biodiesel. SAE 8620 carbon steel, 13 Cr supermartensitic stainless steel and AA 6061-T4 aluminum alloy are more resistant materials in contact with biodiesel and their blends with diesel oil, which can be used, for example, as materials in the construction of transport and storage tanks.
Study of the effects of biodiesel and its blends with diesel oil in metallic materials
Keywords: Aço carbono 8620; Aço inoxidável supermartensítico 13 Cr; Liga de alumínio AA 6061-T4; Misturas diesel/biodiesel; Corrosão; 8620 Carbon steel; 13 Cr supermartensitic stainless steel; AA6061-T4 aluminum alloy; diesel/biodiesel blends; Corrosion; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA